Posterior Reversible Encephalopathy Syndrome due to Hypomagnesemia: A Case Report and Literature Review - Mohamad Almoussa; Angelika Goertzen; Stephan Brauckmann; Barbara Fauser; Christoph W. Zimmermann (Case Reports in Medicine)
Background. Hypomagnesemia can cause various unspecific neurological complications, which can lead to diagnostic confusion. One of these complications is the posterior reversible encephalopathy syndrome (PRES), which is extremely uncommon and has been reported only twice in the English-language literature. Case presentation. We report the case of a 60-year-old man who presented with PRES involving only the cerebellar hemispheres and associated with hypomagnesemia. After excluding all the other possible etiologies of PRES, we started magnesium replacement therapy, which led to a remarkable but fluctuating clinical and chemical improvement. A full recovery with no need for further supplementation was achieved only after discontinuation of a proton pump inhibitor. Conclusions. This case highlights the role of magnesium in the pathophysiology of PRES; thereby, underlying hypomagnesemia should be considered in every PRES case with unclear etiology.